Does Board Independence Matter? Evidence from New Zealand - Hardjo Koerniadi; Alireza Tourani-Rad (Australasian Accounting, Business and Finance Journal, 2012)
This paper examines the effects of the presence of independent directors on firm value using both market-based performance measures (Tobin’s Q ratio and EVA) and accounting-based ratios (ROA and ROE). We find that, instead of adding value, independent directors in New Zealand negatively affect firm value. We also find that, consistent with stewardship theory, independent directors have a positive effect on firm value only when they are in the minority. These findings are important given the increasing trend toward independence in corporate boards around the globe and suggest that board independence may not generally be suitable for countries where managers are considered as active partners along with other stakeholders in companies.
Keywords: Independent directors; firm performance; stewardship theory; EVA